OS DIFERENTES DISCURSOS SOBRE O AUTISMO - PAULA GONÇALVES , JÉSSICA; BEATRIZ ZIMMERMANN MACHADO , JOANA; SCHOCK TEIXEIRA , JULIA; DE VARGAS , NATÁLIA; DA COSTA DIAS , TAMIRES (Salão do Conhecimento, 2020)
Projeto de pesquisa realizado no curso de Psicologia da UNIJUÍ